2022
DOI: 10.1155/2022/2078520
|View full text |Cite
|
Sign up to set email alerts
|

Overall Structural Alteration of Gut Microbiota and Relationships with Risk Factors in Patients with Metabolic Syndrome Treated with Inulin Alone and with Other Agents: An Open-Label Pilot Study

Abstract: Objective. The relative contribution of some products with prebiotic effects, such as inulin, together with medications specific to the human gut microbiome has not been comprehensively studied. The present study determined the potential for manipulating populations in the gut microbiome using inulin alone and combined with other agents in individuals with metabolic syndrome (MetS). The study also assessed whether there is relationship variability in multiple clinical parameters in response to intervention wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…27 A previous study showed that inulin improved glucose and lipid metabolism disorders in ob/ob mice through leptin pathway mediated by Prevotellaceae UCG 001. 28 Another previous study in diabetic rat model reported a suppression of proinflammatory cytokine production upon the administration of inulin attributed to reduced number of Mucispirillum and Ruminiclostridium_6. 24 Similarly, metformin has a suppressive response to proinflammatory cytokine.…”
Section: Resultsmentioning
confidence: 96%
“…27 A previous study showed that inulin improved glucose and lipid metabolism disorders in ob/ob mice through leptin pathway mediated by Prevotellaceae UCG 001. 28 Another previous study in diabetic rat model reported a suppression of proinflammatory cytokine production upon the administration of inulin attributed to reduced number of Mucispirillum and Ruminiclostridium_6. 24 Similarly, metformin has a suppressive response to proinflammatory cytokine.…”
Section: Resultsmentioning
confidence: 96%
“…Inulin‐type fructan supplementation decreased fat mass slightly, but did not significantly change BMI, lipid or glucose homeostasis 106 . Inulin also favourably influenced microbiome composition 107,108 . While in adults no convincing effect on body weight could be observed, in obese children inulin and dietary fibre together with increased exercise showed a significant decrease in weight and body fat 109 .…”
Section: Methodsmentioning
confidence: 95%
“…106 Inulin also favourably influenced microbiome composition. 107,108 While in adults no convincing effect on body weight could be observed, in obese children inulin and dietary fibre together with increased exercise showed a significant decrease in weight and body fat. 109 Resistant starch type 4 (RS4) supplementation positively affected lipid metabolism, potentially by modulating bile acid metabolism and microbiome composition, but not glucose metabolism.…”
Section: Prebioticsmentioning
confidence: 99%
“…Overall, multiple studies agree that a reduction in butyrate producers, including Faecalibacterium, Alistipes, Oscillobacter, Roseburia, and Pseudofavonifractor, in MetS are key contributors to the pathogenic mechanisms of MetS [53]. Indeed, SCFAs, including butyrate, propionate, and acetate, have a particular affinity for G-protein coupled receptors, namely FFAR2 and FFAR3, which regulate satiety and intestinal motility by stimulating the secretion of glucagon-like peptide (GLP) and peptide YY (PYY) from intestinal L-cells [54].…”
Section: Biological Mechanisms Involved In Metabolic Syndromementioning
confidence: 95%